Novel treatment and prophylaxis of uncomplicated urinary tract infections 2 - Naber, Kurt G. (Henry Stewart Talks, 2023)
Prevention of recurrent UTI (cystitis), Factors affecting recurrence, Cystitis and quality of life, Preventative measures for recurrent cystitis, Antimicrobial prophylaxis of recurrent UTI, Effect of increased daily water intake, Probiotics containing specific strains might prevent recurrent UTI, Cranberry products, Uro-Vaxom® enhances the defenses against recurrent UTI, Sublingual MV140 for prevention of recurrent UTIs